Historical context and the criminological imagination: towards a three-dimensional criminology - Yeomans, Henry (Criminology & criminal justice, 2019)
It is widely claimed that criminologists should exercise a ‘criminological imagination’ by connecting individual experiences of crime to social structures and historical context. Despite such claims, criminology is often guilty of a ‘presentism’ that sees the past neglected, ignored or misunderstood. So why and how should criminological research be contextualized historically? This article identifies and examines the functions and forms of historical research within criminology. The article’s significance rests partly in the formulation of an original matrix of forms and functions and its practical utility as a framework for supporting historical contextualization. Additionally, it is ultimately intended that this framework will help construct a more historically sensitive criminology, as attuned to historical context as it is to individual lives and social structures. The creation of this three-dimensional criminology would entail a fuller realization of the criminological imagination, thus significantly enhancing the analytical and socially transformative properties of criminological research broadly.